Комп’ютерний зір у системах дистанційного керування - Філатов, О. Є. (ХНУРЕ, 2023)
The work examines remote control tools using neural networks for image recognition. Machine learning is implemented on the basis of the MediaPipe Hands library, which contains human palm recognition models.
Keywords: комп'ютерний зір; дистанційне керування; машинне навчання